2004
DOI: 10.1177/073401680402900205
|View full text |Cite
|
Sign up to set email alerts
|

Aids Education Needs Assessment: A Comparative Study of Jail and Prison Correctional Officers

Abstract: To ascertain HIV/AIDS knowledge levels and the education needs of correctional officers in jails and state prisons in northwest Florida, a needs assessment instrument was administered in the workplace. State law requirements mandating annual HIV/AIDS training for correctional officers led to a hypothesis that state prison correctional officers would have greater knowledge levels than jail correctional officers, who do not have regularly scheduled training as there is no mandated program on the local level. On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…A review of the literature regarding correctional officers' knowledge of HIV/ AIDS and how risk is perceived in the workplace uncovered eight related articles. Four articles studied corrections institutions in the United States (Kamerman, 1991;Keeton, 2004;Mahaffey & Marcus, 1995;McIntyre et al, 1999) and the others examined prisons in Europe (Dillon & Allwright, 2005;Ferguson, 1997;McKee, Markova, & Power, 1995;Rotily et al, 2001).…”
Section: Hiv Knowledge and Perceived Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of the literature regarding correctional officers' knowledge of HIV/ AIDS and how risk is perceived in the workplace uncovered eight related articles. Four articles studied corrections institutions in the United States (Kamerman, 1991;Keeton, 2004;Mahaffey & Marcus, 1995;McIntyre et al, 1999) and the others examined prisons in Europe (Dillon & Allwright, 2005;Ferguson, 1997;McKee, Markova, & Power, 1995;Rotily et al, 2001).…”
Section: Hiv Knowledge and Perceived Riskmentioning
confidence: 99%
“…Staff who had HIV training had generally the same level of knowledge as staff who did not have training (Dillon & Allwright. 2005;Keeton. 2004).…”
Section: Hiv Knowledge and Perceived Riskmentioning
confidence: 99%
“…In researching correctional staff who worked at a prison hospital that provided treatment to HIV/AIDS inmates, Kamerman (1991) found information and training reduced fears of working with individuals with an infectious disease. Dillon and Allwright (2005), Hartley et al (2013), Keeton (2004), and Lambert and Paoline (2005) also concluded more information and training on infectious disease and its control are needed for staff. In-depth information on what is being done to address inmate infectious diseases to protect staff and other inmates needs to be provided.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, worldwide public health campaigns have been more effective in reaching populations most at risk with prevention, outreach, and treatment advances. However, most corrections-based HIV/AIDS education in the United States implements a “one-size-fits-all” approach (Keeton, 2004; Swartz et al, 2004). Results of the current study underscore gender differences in perception that persist among inmates with respect to perceived risk of seroconversion and access to HIV education.…”
Section: Discussionmentioning
confidence: 99%